Evidence for benefits and risks of tadalafil as a non-prescription medicine: review and evaluation using the Group Delphi technique to achieve consensus amongst clinical experts - Miller, Kurt; May, Uwe; Beecken, Wolf-Dietrich; Hatzichristodoulou, Georgios; Böhm, Michael; Fink, Stefan (Frontiers in Pharmacology, 2023)
An evidence-based consensus meeting was held with urologists, a pharmacist and a cardiologist to perform a structured benefit-risk analysis of reclassifying tadalafil, a phosphodiesterase type 5 (PDE5) inhibitor for treatment of erectile dysfunction (ED), to be available without prescription in Germany. As per the Brass process endorsed by regulatory authorities, an evidence-based Brass value tree was developed, which identified the incremental benefits and risks that should be considered above the safety and efficacy evidence required for prescription medicines. During the Group Delphi consensus meeting, the expert panel rated the likelihood and clinical impact of each benefit and risk on a scale of 0 (none) to 3 (high). Overall attribute scores were calculated from the product of the mean likelihood and mean clinical impact scores giving a possible score of 0 to 9. The overall benefit attribute scores ranged from 2.8 to 5.4. The overall risk attribute scores ranged from 0.2 to 2.2 though most were 1.0 or less (3 or more is generally considered to be of concern). On balance, the independent meeting scored the benefits of reclassification of tadalafil higher than the risks and considered the risk mitigation strategies of the packaging label and patient information leaflet (PIL) sufficient.